2022
DOI: 10.1088/1748-9326/ac44c5
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale forest conservation and restoration programs significantly contributed to land surface greening in China

Abstract: China has implemented a portfolio of large-scale forest conservation and restoration programs (FCRPs) to advance the sustainable management of forests. However, the contributions of these programs to forest recovery and land surface greening were generally evaluated on a local scale, which hindered the systematic planning of FCRPs. In this study, we analyzed the spatiotemporal patterns of tree cover change before and after the intensification of FCRPs using Mann-Kendall test and Theil-Sen's slope estimator. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…In addition to spatiotemporal changes, we also detected the timing and trend shifts of greenness time series to reveal abrupt changes in vegetation during 2000-2020. Our results showed that the year when the turning point of greenness trend occurred spanned from 2005 to 2014 and exhibited heterogeneity across urban and rural areas (figure 6(a)), although previous studies tend to set the same year for the turning points of greenness trends for all regions of China (Ma et al 2019, Zhao et al 2022.…”
Section: Detection Of Turning Point and Trends Shift With Ndvi Time S...mentioning
confidence: 61%
See 4 more Smart Citations
“…In addition to spatiotemporal changes, we also detected the timing and trend shifts of greenness time series to reveal abrupt changes in vegetation during 2000-2020. Our results showed that the year when the turning point of greenness trend occurred spanned from 2005 to 2014 and exhibited heterogeneity across urban and rural areas (figure 6(a)), although previous studies tend to set the same year for the turning points of greenness trends for all regions of China (Ma et al 2019, Zhao et al 2022.…”
Section: Detection Of Turning Point and Trends Shift With Ndvi Time S...mentioning
confidence: 61%
“…Urban and rural areas together form the fabric of China's landscape ecology while exhibiting distinct vegetation patterns due to different anthropogenic activities. In recent decades, China has undergone rapid urbanization, accompanied by a large number of people moving from rural to urban areas (Zhao et al 2022, Zhang et al 2022a. This process has been shown to cause a substantial loss in vegetation productivity in urban areas via the expansion of impervious surfaces (He et al 2014, Liu et al 2020b.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations